Hantavirus pulmonary syndrome in Santa Cruz, Bolivia: outbreak investigation and antibody prevalence study. - Joel M Montgomery; Patrick J Blair; Darin S Carroll; James N Mills; Alberto Gianella; Naomi Iihoshi; Ana M Briggiler; Vidal Felices; Milagros Salazar; James G Olson; Raisa A Glabman; Daniel G Bausch (Public Library of Science (PLoS), 2012)
We report the results of an investigation of a small outbreak of hantavirus pulmonary syndrome in 2002 in the Department of Santa Cruz, Bolivia, where the disease had not previously been reported. Two cases were initially reported. The first case was a physician infected with Laguna Negra virus during a weekend visit to his ranch. Four other persons living on the ranch were IgM antibody-positive, two of whom were symptomatic for mild hantavirus pulmonary syndrome. The second case was a migrant sugarcane worker. Although no sample remained to determine the specific infecting hantavirus, a virus 90% homologous with Río Mamoré virus was previously found in small-eared pygmy rice rats (Oligoryzomys microtis) trapped in the area. An antibody prevalence study conducted in the region as part of the outbreak investigation showed 45 (9.1%) of 494 persons to be IgG positive, illustrating that hantavirus infection is common in Santa Cruz Department. Precipitation in the months preceding the outbreak was particularly heavy in comparison to other years, suggesting a possible climatic or ecological influence on rodent populations and risk of hantavirus transmission to humans. Hantavirus infection appears to be common in the Santa Cruz Department, but more comprehensive surveillance and field studies are needed to fully understand the epidemiology and risk to humans.